GAMBARAN PERILAKU HIDUP SEHAT IBU YANG MEMILIKI BALITA DI WILAYAH KERJA PUSKESMAS UBUD I, KABUPATEN GIANYAR BALI TAHUN 2014 - Yuhanantini Gopal Kishnam (Intisari Sains Medis, 2015)
10 diseases in Puskesmas Ubud I, which ranks 9th with a number of 687 cases. The prevalence of diarrhea in infants in Puskesmas Ubud I 220 children or 6,1%.Methods: This study used a descriptive cross-sectional design. Data were obtained from interviews with a structured questionnaire. Respondents were 45 mothers who has toddler chosen by simple random sampling. Data were analyzed using statistical program and presented in tabular form and narrative.Results: Most respondents (88.9%) already have hand washing behavior, but the method used is still much less good. Most respondents do not have a washing behavior as many as 73,3%. As many as 60% of respondents own behavior wash cutlery and most of the methods used is good. 68,9% of respondents have a water boiling behavior and methods are good. 82.2% respondents do not have a good food storage behavior.Conclusions: The majority of respondents do not have a washing behavior, as many as 73,3% of respondents do not have the habit of washing foods and most respondents do not have a good food storage behavior that 82,2% of respondents did not know how to store good food.